2013
DOI: 10.1111/den.12140
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the accuracy of endoscopic transpapillary sampling methods for bile duct cancer

Abstract: Endoscopic transpapillary sampling methods are more accurate for longer or elevated (non-flat) biliary cancerous lesions than for shorter or flat lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
5
31
2
Order By: Relevance
“…Brush cytology has a wide sensitivity ranging from 26% to 80% and a specificity of 83–100% for bile duct cancer . The results found in the study by Nishikawa et al . are representative of the results noted in the literature.…”
supporting
confidence: 82%
“…Brush cytology has a wide sensitivity ranging from 26% to 80% and a specificity of 83–100% for bile duct cancer . The results found in the study by Nishikawa et al . are representative of the results noted in the literature.…”
supporting
confidence: 82%
“…reported that elder age, higher serum bilirubin levels and the presence of mass on cross‐sectional imaging are independent predictive factors for a positive diagnosis by brush cytology. Nishikawa et al . reported that a non‐flat biliary cancerous lesion was an independent predictor for a positive diagnosis of bile duct cancer by brush cytology and forceps biopsy in bile duct cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to clarify the predictive factors associated with a positive diagnosis by brush cytology and forceps biopsy in the assessment of alternative sampling procedures after a negative result by brush cytology and forceps biopsy. Several studies have reported predictive factors for brush cytology and forceps biopsy in MBS, such as elder age, high serum bilirubin levels, non‐flat lesions and mass on the imaging examination, etc . However, these studies also included relatively few patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, higher sensitivities were reported by Urbano et al [19], Arvanitakis et al [20], and Temiño López-Jurado et al [10] (65, 63, and 61%, respectively). Several factors have been highlighted to explain this large variability in sensitivity, such as the endoscopic technique, type of brush, use of dilatation and basket, cytological techniques, and cytological criteria for malignancy, interpathologist variation for biliary cytology interpretation, patient age, and the type, localization, and length of the tumor [1, 10, 13, 15, 18, 21, 22, 24]. In the current study, we found an overall sensitivity of 52.5%, a result in line with the previous literature.…”
Section: Discussionmentioning
confidence: 99%